Is in vivo amyloid distribution asymmetric in primary progressive aphasia?. Issue 3 (2nd February 2016) - Martersteck, Adam; Murphy, Christopher; Rademaker, Alfred; Wieneke, Christina; Weintraub, Sandra; Chen, Kewei; Mesulam, M.‐Marsel; Rogalski, Emily; ,
Abstract : We aimed to determine whether 18 F‐florbetapir amyloid positron emission tomography imaging shows a clinically concordant, left‐hemisphere–dominant pattern of deposition in primary progressive aphasia (PPA). Elevated cortical amyloid (Aβ + ) was found in 19 of 32 PPA patients. Hemispheric laterality of amyloid burden was compared between Aβ + PPA and an Aβ + amnestic dementia groups (n = 22). The parietal region showed significantly greater left lateralized amyloid uptake in the PPA group than the amnestic group ( p < 0.007), consistent with the left lateralized pattern of neurodegeneration in PPA. These results suggest that the cortical distribution of amyloid may have a greater clinical concordance than previously reported. ANN NEUROL 2016;79:496–501